Modification of Coal Samples with Bursting Liability Subjected to Microwave Irradiation - Yingyuan Wen; Weiming Guan; Hongchao Zhao; Honglin Liu; Huwei Li; Qi Qi (Shock and Vibration)
This paper introduces the innovative technique to release the bursting liability of coal seam via microwave irradiation. To verify the feasibility of this environment-friendly technique, a series of laboratory tests incorporating acoustic emission (AE) investigation were carried out. Test results indicated that both the uniaxial compressive strength (UCS) and bursting energy index of raw and water-soaked coal samples were significantly reduced. In particular, the bursting liability was reduced by one level when the values of UCS were compared, the evidence of which is the variation of wave velocities of tested coal samples. It can also be found from the events and hits in the complete stress-strain curve and the cumulative curve of acoustic emission that the elastic modulus of the raw and water-soaked coal samples subjected to microwave irradiation decreased by 58.42% and 29.63%, respectively. This facilitates the entry into the stage of stable crack propagation more quickly, the growth rate and size of the cracks were slower and more uniform, and there were no smaller coal fragments ejecting during the failure process of the coal samples. Meanwhile, the proportion of high-energy events released in coal samples experienced a decline after the treatment of the microwave. Moreover, microwave heating principally promoted the initiation and expansion of microcracks in coal samples under the influence of microwave power of 1 kW and a heating time of 120s, which may cause the overall damage of large fractures to break into multiple small and medium cracks. Based on the experimental results, the conceptual process of using microwave in weakening the bursting liability of coal seam was then proposed, which will be the meaningful reference for microwave-assisted oil recovery and coal bed methane production.